Hearing impairment and audiovisual speech integration ability: a case study report - Altieri, Nicholas; Hudock, Daniel (Frontiers in Psychology, 2014)
Research in audiovisual speech perception has demonstrated that sensory factors such as auditory and visual acuity are associated with a listener’s ability to extract and combine auditory and visual speech cues. This case study report examined audiovisual integration using a newly developed measure of capacity in a sample of hearing-impaired listeners. Capacity assessments are unique because they examine the contribution of reaction-time (RT) as well as accuracy to determine the extent to which a listener efficiently combines auditory and visual speech cues relative to independent race model predictions. Multisensory speech integration ability was examined in two experiments: An open-set sentence recognition and a closed set speeded-word recognition study that measured capacity. Most germane to our approach, capacity illustrated speed-accuracy tradeoffs that may be predicted by audiometric configuration. Results revealed that some listeners benefit from increased accuracy, but fail to benefit in terms of speed on audiovisual relative to unisensory trials. Conversely, other listeners may not benefit in the accuracy domain but instead show an audiovisual processing time benefit.